2021
DOI: 10.3390/jcs6010003
|View full text |Cite
|
Sign up to set email alerts
|

Implementation on a Preparation and Controlled Compaction Procedure for Waste-Fiber-Reinforced Raw Earth Samples

Abstract: Earth bricks are a traditional eco-friendly construction material. In this study, harbor-dredged sediments were used along with hemp shiv to develop a brick manufacturing procedure and compaction techniques to produce durable earth bricks for the valorization of waste hemp shiv and dredged sediments. Prismatic specimens of size 4 × 4 × 16 cm3 were manufactured with Dunkirk sediments after analyzing their suitability for earth bricks according to the French standard for flexural strength test to observe the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Toughness index increases with increasing fiber content. From literature, crude bricks with Dunkirk port dredged sediments with 1%, 2%,3%,4% and 5% hemp shiv content have toughness values 2.42, 2.78, 2.74, 3.34, and 3.33 respectively (Hussain et al, 2020). Type of fibers and sediments significantly affect the toughness of crude bricks.…”
Section: Toughness Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Toughness index increases with increasing fiber content. From literature, crude bricks with Dunkirk port dredged sediments with 1%, 2%,3%,4% and 5% hemp shiv content have toughness values 2.42, 2.78, 2.74, 3.34, and 3.33 respectively (Hussain et al, 2020). Type of fibers and sediments significantly affect the toughness of crude bricks.…”
Section: Toughness Indexmentioning
confidence: 99%
“…Compaction of crude bricks cane be done by static, vibratory and dynamic loading. Bricks compacted with dynamic loadings have good tensile strength (Hussain et al, 2020). For the compaction of crude bricks with normal Proctor energy, optimum water content of sediments found through Proctor test can be used for preparing sediments mixture (Bruno et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified various types of natural and synthetic fibers that could improve the compressional strength [12][13][14]. Laborel-Preneron et al reported on mixtures of polyester fibers of 12 mm in length with soil at relative amounts of fiber ranging from 0-1% and showed that inclusion of polyester fibers increased the strength of the soil until the ratio of fibers added was at 0.5%.…”
Section: Introductionmentioning
confidence: 99%